1989
DOI: 10.1073/pnas.86.24.10090
|View full text |Cite
|
Sign up to set email alerts
|

Regression of adjuvant-induced arthritis in rats following bone marrow transplantation.

Abstract: Total body irradiation followed by bone marrow transplantation was found to be an effective treatment for adjuvant arthritis induced in rats. This treatment is most effective when applied shortly after the clinical manifestation of arthritis--i.e., 4-7 weeks after administration of Mycobacterium tuberculosis. Transplantation of bone marrow at a later stage results in a limited recovery, in that the inflammatory reaction regresses but the newly formed excessive bone is not eliminated. Local irradiation of the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(48 citation statements)
references
References 24 publications
1
45
0
2
Order By: Relevance
“…Alternatively, myeloablative and nonmyeloablative conditioning are highly immune-depleting, and used in conjunction with autologous HSCT (aHSCT) for recovery of hematopoiesis, can provide an "immunologic reset." This avoids the risks of allogeneic BMT/HSCT and subsequent GVHD but alleviates autoimmune disease experimentally [2][3][4] and clinically (reviewed by Coleman and Steptoe 5 ). In multiple sclerosis, approximately 70% of patients treated with aHSCT remain progression-free 3 years after treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, myeloablative and nonmyeloablative conditioning are highly immune-depleting, and used in conjunction with autologous HSCT (aHSCT) for recovery of hematopoiesis, can provide an "immunologic reset." This avoids the risks of allogeneic BMT/HSCT and subsequent GVHD but alleviates autoimmune disease experimentally [2][3][4] and clinically (reviewed by Coleman and Steptoe 5 ). In multiple sclerosis, approximately 70% of patients treated with aHSCT remain progression-free 3 years after treatment.…”
Section: Introductionmentioning
confidence: 99%
“…It was clearly shown that the transplantation protects the cited conditions from relapse [10][11][12]. Similar effect was shown in autoimmune diseases with other target organs [13].…”
Section: Introductionmentioning
confidence: 55%
“…Autologous HSCT, however, avoids GVHD and other risks associated with allogeneic or MHC-mismatched HSCT, making it more applicable to clinical use for autoimmune diseases. Syngeneic and autologous HSCT was tested in animal models and found effective in EAE and experimental arthritis [29][30][31].…”
Section: Haematopoietic Stem Cell Transplantation For Autoimmune Diseasementioning
confidence: 99%